Design Strategies From Industrial Regeneration Towards Community Health: Learning From the Montreal Ephemeral Ecosystem - Covatta, Alice (Sens public)

(untitled) (Département des littératures de langue française, 2024)
Following the recession of manufacturing, shipping and bank sectors that started in the 1980s that emptied its inner core, Montreal has experienced a rapid urban transformation pushed by the knowledge economy, particularly in the fields of education, arts, video gaming and artificial intelligence. Since the 2010s Montreal has become an international example for European post-industrial cities for the ability to renovate itself, injecting new activities into crumbling urban sectors, stimulating urban growth and reinventing the city identity. If Montreal was the example of an industry-driven city in the past, nowadays it is all about the metamorphosis of its post-industrial legacy. A key urban tool as part of this process is the transitional urbanism adopted in recent years by the city government in collaboration with different private-public actors. The research aims to decipher the dynamics subtended in the process with the involvement of community organisations, artists and entrepreneurs through diverse case studies that have been enacted in recent years of transitional urbanism. At the heart of the theoretical background and findings of the case studies analysis lie two interconnected and captivating avenues: firstly, a collective urban imaginary based on temporal connectivity toward a social, physical, and ecological harmony aiming to bind the context and mitigate the impact of future urban action; secondly, a trap for a low-budget permanent urbanism that instils a sense of precariousness and uncertainty to the users. The research objective is to provide guidelines for comparative studies with European post-industrial cities, especially on how an ephemeral ecosystem can link past-present-future in order to achieve a sustainable development that positively impacts community health.